World Trade Organization Activities in Equatorial Africa - Ulrich, Tadeáš; Hnát, Pavel, 1981-; Agustina, Shirley Basauli; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This thesis explores the WTO’s efforts to address trade challenges faced by developing countries, focusing on the Aid for Trade initiative and its impact in Equatorial Africa. The thesis analyzes trade-related issues from developing countries at global, regional, national, and project perspectives. Through case studies of specific projects in Ghana, Kenya and Nigeria, the study provides insights into how the WTO’s initiatives contribute to supporting trade and development in Sub-African economies.
Vedoucí práce: Pavel Hnát
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses